2017
DOI: 10.1093/shm/hkx016
|View full text |Cite
|
Sign up to set email alerts
|

Personalities, Preferences and Practicalities: Educating Nurses in Wound Sepsis in the British Hospital, 1870–1920

Abstract: Summary The history of nursing education has often been portrayed as the subordination of nursing to medicine. Yet, as scholars are increasingly acknowledging, the professional boundaries between medicine and nursing were fluid in the nineteenth and early twentieth centuries, when both scientific knowledge and systems of nurse training were in flux. Through its focus on the role of medical practitioners in educating nurses in wound sepsis at four British hospitals between 1870 and 1920, this article attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Germ theoretic approaches to disease causation provided renewed justification for such practices, rationalising surgical methods which had already become well-established [14].Until the mid-nineteenth century, nursing was not an activity which was thought to demand particular skill or formal training. As recent historical research has shown, nurse education in wound sepsis remained largely determined by local factors -including the personal inclinations of individual instructors -at a time when the details of bacteriology and their implications for practice were in flux [15]. Against this backdrop, new dressings such as Elastoplast and 'Gamgee Tissue' -a preparation of cotton wool and surgical gauze developed in 1880 by J. Sampson Gamgee, a surgeon based at the Queen's Hospital, Birmingham -provided alternative ways of managing both acute and chronic wounds [16].As well as development of specific surgical innovations, often during the context of warfare, relevant non-surgical ideas included both nursing and sanitary reform, in particular from the Crimea [17].…”
mentioning
confidence: 99%
“…Germ theoretic approaches to disease causation provided renewed justification for such practices, rationalising surgical methods which had already become well-established [14].Until the mid-nineteenth century, nursing was not an activity which was thought to demand particular skill or formal training. As recent historical research has shown, nurse education in wound sepsis remained largely determined by local factors -including the personal inclinations of individual instructors -at a time when the details of bacteriology and their implications for practice were in flux [15]. Against this backdrop, new dressings such as Elastoplast and 'Gamgee Tissue' -a preparation of cotton wool and surgical gauze developed in 1880 by J. Sampson Gamgee, a surgeon based at the Queen's Hospital, Birmingham -provided alternative ways of managing both acute and chronic wounds [16].As well as development of specific surgical innovations, often during the context of warfare, relevant non-surgical ideas included both nursing and sanitary reform, in particular from the Crimea [17].…”
mentioning
confidence: 99%
“…From November till after the winter clothing was served out, the supply was very deficient, either of shirts, socks, or other articles of underclothing ' (p. 42). (e.g., management of wound sepsis) and its value in health promotion to patients (Howell et al, 2013;Jones et al, 2018). Florence…”
Section: Discussionmentioning
confidence: 99%
“…From November till after the winter clothing was served out, the (e.g., management of wound sepsis) and its value in health promotion to patients (Howell et al, 2013;Jones et al, 2018). Florence…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What happened when antiseptics ‘left the clinic,’ to borrow a recent phrase from Marina Hilber (2022)? In the last two decades of the nineteenth century Lister's antiseptic practices were introduced into midwifery, nursing, and a variety of other medical fields (Hanley 2013; Jones et al 2017). Laboratory studies of disease-causing microorganisms and the effectiveness of carbolic acid all pointed to one conclusion.…”
Section: Introductionmentioning
confidence: 99%